Views from the margins: Theorising the experiences of black working-class students in academic development in a historically white South African university - Mlamuli N. Hlatshwayo; Kehdinga G. Fomunyam (The Journal for Transdisciplinary Research in Southern Africa, 2019)
A significant amount of South African literature on academic development often focuses on the ideological and theoretical shifts that have occurred within the academic development field across different periods in the country – tracing different phases within the field, broadly termed, ‘academic support’, ‘academic development’ and ‘higher education development’. One of the gaps that have been identified in this literature is often the silence regarding the experiences of the black students themselves in academic development, and to what extent being in the programme has made a difference to their university experiences. This article attempts to fill this gap by critically exploring and theorising the complex experiences of black working-class South African students in an academic development programme in a historically white higher education institution. To effectively make sense of their experiences, French philosopher Pierre Bourdieu’s theory on capital was employed in this article. Participants were purposely recruited using snowball sampling and 32 black working-class students participated in the study. The findings of this study suggest that academic development in a historically white university is a complex field of forces that require further critical interrogation and theorisation. Students’ experiences of academic development are often complex and at times contradictory with some seeing the value of the programme, and others rejecting it and looking at it as an extension of their marginality in a historically white higher education institution.